Perkuatan Struktur Beton Bertulang Dengan Metode FRP dan Concrete Jacketing - Parmo, Parmo; Hakim, Abdul; Yusrianti, Yusrianti; Wicaksono, Bagus Gilbran Antoni (Department of Civil Engineering, Diponegoro University, 2025)
Applying the latest building earthquake resistance codes, SNI 1726:2019 to the reinforced concrete structure of the Islamic Center Building shows several column and beam elements that required strengthening, including beam B1, column K-Bordes, and column K3. This case study research aims to determine the appropriate strengthening method, the thickness of the additional column dimensions with the concrete jacketing method, and the number of FRP layers for columns and beams. Systematic steps in the study process starting from collecting existing data, field investigation, evaluation of structures in accordance with ASCE 41-17, structural modeling with SAP2000, and data analysis. The analysis showed that Column K-Bordes was confined with a thickness of 100 mm using concrete jacketing, Column K3 was strengthened with one layer of GFRP at the plastic hinge, and Beam B1 was strengthened with two layers of GFRP at the support area. Pull-off test showed GFRP adhesion strength values to concrete of 3.80 MPa (Beam B1) and 2.50 MPa (Column K3). This approach proves the effectiveness of the combined reinforcement method in increasing the structural capacity according to the latest earthquake codes.